2022
DOI: 10.1007/s10643-022-01309-2
|View full text |Cite
|
Sign up to set email alerts
|

Music Uses in Preschool Classrooms in the U.S.: A Multiple-Methods Study

Abstract: This study reports preschool educators' uses of music in educational settings, as well as challenges faced in incorporating music in the classroom in the U.S. Through a multiple-methods approach, data from two focus groups (N1 = 8, N2 = 6) and a survey (N = 119) are used to gain insight into how frequently preschool educators in the US use various types of music activities in their classrooms, for what purposes they do so, and what challenges they face in doing so. This study also sheds light on the current li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…In terms of challenges teachers face, previous research provides important considerations including a lack of musical expertise and confidence (Bond, 2012; Kim & Kemple, 2011) and a lack of resources for musical instruction (Rajan, 2017). These issues were echoed in our findings, as teachers reported a lack of access to musical instruments, visuals or manipulatives for musical activities, and quality technology for music uses, and also noted lack of access to music in different languages for the DLLs in their classrooms (Kirby et al, 2022). In sum, our results coupled with previous research suggest that ECE teachers would use music more if the challenges they faced, including a lack of music resources, were reduced.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…In terms of challenges teachers face, previous research provides important considerations including a lack of musical expertise and confidence (Bond, 2012; Kim & Kemple, 2011) and a lack of resources for musical instruction (Rajan, 2017). These issues were echoed in our findings, as teachers reported a lack of access to musical instruments, visuals or manipulatives for musical activities, and quality technology for music uses, and also noted lack of access to music in different languages for the DLLs in their classrooms (Kirby et al, 2022). In sum, our results coupled with previous research suggest that ECE teachers would use music more if the challenges they faced, including a lack of music resources, were reduced.…”
Section: Introductionmentioning
confidence: 60%
“…Given the literature reviewed above, we are committed to supporting educators who opt to use music as a tool for early childhood language and literacy development, especially in linguistically diverse classrooms. The findings of our multiple‐methods study of music use in early childhood classrooms (Kirby et al, 2022) showed that teachers know the value of music in supporting language and literacy development and use music frequently. However, teachers also described challenges they faced in using music to the extent that they would like to and in the ways that they would like to.…”
Section: Promoting Language and Literacy Through Music In Classroomsmentioning
confidence: 91%
See 2 more Smart Citations
“…Otherwise, the modernization of teaching means is not feasible, and environment-friendly ecological vocal music teaching is out of the question. Colleges and universities should proceed from the teaching reality, according to the specific situation of students' classroom teaching and extracurricular practice, strengthening the construction of teaching facilities, such as upright piano, grand piano, multimedia classroom, MIDI classroom, concert hall, audio and video reference room, and professional recording studio [ 23 , 24 ]. For example, the teacher can optimize classroom teaching through a computer-aided method and its powerful multitrack recording function.…”
Section: Construction Of Environment-friendly Ecological Vocal Music ...mentioning
confidence: 99%